Axiological potential of adjective russ. ural’skiy - Vepreva, Irina (Przegląd Wschodnioeuropejski, 2018)
The article presents the specifics of the contextual use of the relative adjective Ural in qualitative meaning on the material of federal and regional newspapers published in the Sverdlovsk region. The axiological potential of the ottoponymic adjective is determined by the essential attributes of space as the fundamental reality of human existence. The analyzed material has shown that the augment of qualitatively-evaluative connotations of the relative adjective occurs due to the guidance of the value meanings by the context represented as the set of the typical compatibility of the word, due to the reflexive discussion of everything connected with the Ural region. At the same time, the axial “small homeland” is the nuclear component of the axiosphere “Ural”, verbally expressed by our lexemes our, native, nearest. In addition, the expression of qualitative characteristics of the adjective Ural is associated with a mental predetermined evaluation of abstract concepts. Set expressions (for example, the Ural character) functioning in the speech, the explication of the graduation of the relative adjective in the speech help to actualize the value conceptions about the Urals and their inhabitants formed in the consciousness of the native speaker.